Regional integration in the Americas: State of play, lessons, and ways forward - Antoni Estevadeordal; Matthew Shearer; Kati Suominen (Asian Development Bank Institute (ADBI), 2011)
The Americas have been a key driver of regional trade agreements (RTAs) since the 1990s. This study considers the effect of these agreements on trade liberalization, and the lessons that this offers for other parts of the world, notably Asia. It finds broad geographical coverage of RTAs in the Americas, and evidence that these agreements have broadened and deepened liberalization. It stresses the importance of looking beyond tariffs on goods, to consider liberalization of services and removal of non-tariff barriers, both for academics assessing the true extent of liberalization, and for policymakers looking to ensure well-functioning RTAs. It suggests that RTAs can encourage broader liberalization in Asia, but some sectors will be resistant to liberalization. Moreover, efforts must be made to harmonize the provisions of RTAs, to avoid costly multiplication of rules and to ensure a web of bilateral deals does not undermine multilateral trade.
Keywords: F13; F15; F36; F42; J44; 330; Handelsabkommen; Außenhandelsliberalisierung; Lateinamerika; Vergleich; Handelsregionalismus; Asien